Wiesztortowie z Podbrzezia i Bakszt w Wielkim Księstwie Litewskim w świetle źródeł z II połowy XV i I połowy XVI wieku = Wiesztortowicz of Podbrzezie and Bakszty in the Grand Duchy of Lithuania - Towpik, Paweł Szymon (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Research which was done so far proved that on the territory of the Grand Duchy of Lithuania existed at least several families named Wiesztort or Wiesztortowicz (Westortowicz). Wiesztortowicz is a patronymic name. Both name variations appear in the original documents. Most of the found Wiesztort/Wiesztortowicz belonged to higher class called boyars however there were found also families belonging to town people or peasantry. Hanko Wiesztortowicz was the first known member of the family. As a witness he was mentioned in a document issued in Łyntupy and dated on 1459. This document referred to Andruszko Dowgirdowicz, owner of Świrany and Łyntupy, who made donations to a church in Łyntupy.
Keywords: Wielkie Księstwo Litewskie; 15-16 w.